KEEFEKTIFAN PBL BERBANTUAN FUN THINKERS BOOK TERHADAP KEMAMPUAN BERPIKIR KREATIF SISWA 3 SEKOLAH DASAR - Dewi Marta Agustina; Kartika Yuni Purwanti (JANACITTA, 2022)
This study aims to reveal the effectiveness of the problem based learning model assisted by the media fun thinkers book on increasing students' creative thinking skills. The design of this research is a Quasi Experiment type of Nonequivalent Control Group Design. The population in this study were students of class III SDN Sidomulyo 4 as many as 2 classes. The samples in this study were class III A and III B SDN Sidomulyo 4. The sampling technique used in this study was taken using a purposive sampling technique which is included in non-probability sampling. The data analysis techniques used were normality test, homogeneity test, independent sample t-test, simple linear regression test and paired sample t-test. The results of this study indicate that: (1) There are differences in learning using a problem based learning model assisted by the media fun thinkers book on students' creative thinking abilities with a significance of 0.001 < 0.05 using the independent sample t-test. (2) There is an effect of using the problem based learning model with the help of the media fun thinkers book on students' creative thinking abilities. This is indicated by a significance result of 0.015 < 0.05 using a simple linear regression test. (3) Improving the results of students' creative thinking skills using a problem based learning model assisted by fun thinkers book media in class III SDN Sidomulyo 4 with a significance of 0.000 < 0.05 by using the paired sample t-test. So, the key is that the problem-based learning model assisted by the fun thinker book is effective in improving the creative thinking skills of grade III students.